PENENTUAN GEOMETRI JENJANG DI KUARI PENAMBANGAN ANDESIT BLOK A SITE SOMOREJO, CV. GUNUNG MULIA, DESA SOMOREJO, KECAMATAN BAGELEN, KABUPATEN PURWOREJO, PROVINSI JAWA TENGAH - Rezkie, Hendra; Widodo, Priyo (Prosiding Seminar Teknologi Kebumian dan Kelautan, 2019)
CV. GUNUNG MULIA is one of the business entities engaged in the Andesite mining industry. The area of the miningÂ is 11.1 ha, which is located in Somorejo Village, Bagelen District, Purworejo Regency, Central Java Province. CV. GUNUNG MULIA Blok A Site Somorejo uses a surface mining system with quarry mining methods. Until now mining activities at the research location are still in the development stage. In designing a quarry, an analysis of slope stability is needed. Excavation activities on the slope will cause changes in the values of forces acting on the slope which results in disruption of slope stability so that the slope is potentially failure. At present the slope conditions at the Blok A Site Somorejo mining site have not been designed in stages. For this reason, it is necessary to design a safe level geometry in accordance with rock mass conditions and applicable regulations.